2023
DOI: 10.1002/lno.12357
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen depletion and sediment respiration in ice‐covered arctic lakes

Abstract: Processes regulating the rate of oxygen depletion determine whether hypoxia occurs and the extent to which greenhouse gases accumulate in seasonally ice-covered lakes. Here, we investigate the oxygen budget of four arctic lakes using high-frequency data during two winters in three shallow lakes (9-13 m maximal depth) and four winters in 24 m deep main basin of Toolik Lake. Incubation experiments measured sediment metabolism. Volume-averaged oxygen depletion measured in situ was independent of water temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…2FB Lake underwent unusually rapid oxygen depletion, with bottom‐water anoxia developing only 4 and 11 days after freeze‐up in 2019 and 2020, respectively. Arctic lakes of similar depth have either not developed winter deepwater anoxia (Michaud & Apollonio, 2022) or only experienced near‐bottom depletion weeks to months after freeze‐up (Bégin et al., 2021; Palmer et al., 2019; Schwefel et al., 2023) with similar observations at lower latitudes (Couture et al., 2015; Robarts et al., 2005; Terzhevik et al., 2010). Deepwater oxygen depletion rates in 2FB Lake (0.8–2.6 mg L −1 day −1 ) greatly exceeded those of Alaskan lakes, which ranged from 0.1 to 0.3 mg L −1 day −1 (Schwefel et al., 2023).…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…2FB Lake underwent unusually rapid oxygen depletion, with bottom‐water anoxia developing only 4 and 11 days after freeze‐up in 2019 and 2020, respectively. Arctic lakes of similar depth have either not developed winter deepwater anoxia (Michaud & Apollonio, 2022) or only experienced near‐bottom depletion weeks to months after freeze‐up (Bégin et al., 2021; Palmer et al., 2019; Schwefel et al., 2023) with similar observations at lower latitudes (Couture et al., 2015; Robarts et al., 2005; Terzhevik et al., 2010). Deepwater oxygen depletion rates in 2FB Lake (0.8–2.6 mg L −1 day −1 ) greatly exceeded those of Alaskan lakes, which ranged from 0.1 to 0.3 mg L −1 day −1 (Schwefel et al., 2023).…”
Section: Discussionmentioning
confidence: 85%
“…Major ion concentrations were key drivers of the density gradients and water column stability of 2FB Lake. Solute gradients in cold lakes affect mixing depths prior to and following ice‐off (Cortés & MacIntyre, 2020; Schwefel et al., 2023), and many features of 2FB Lake's temperature stratification indicated that such gradients influenced the unusual under‐ice and summer thermal structures. Higher solute concentrations at depth allowed three unusual thermal structures: stable stratification despite surface temperatures of ∼4°C; inverse temperature stratification in summer 2021 despite water temperatures >6°C; and the mid‐depth temperature maxima.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations